2014
DOI: 10.1093/ntr/ntu132
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Water Pipe Is Not an Alternative to Other Tobacco or Substance Use Among Adolescents: Results From a National Survey in Sweden

Abstract: Water pipe use among adolescents in Sweden is not a recreational tobacco use alternative to cigarettes and should be regarded as a marker of multiple substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Thirty studies from 19 countries reported on ‘other’ defined prevalence measures[ 35 , 69 , 79 , 81 , 82 , 85 , 91 98 , 108 , 112 , 120 132 ], the details of which are presented in Table G in S1 File . Sixteen studies from ten countries did not specific the waterpipe prevalence measure[ 88 , 123 , 129 , 133 – 145 ], the details of which are presented in Table H in S1 File .…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies from 19 countries reported on ‘other’ defined prevalence measures[ 35 , 69 , 79 , 81 , 82 , 85 , 91 98 , 108 , 112 , 120 132 ], the details of which are presented in Table G in S1 File . Sixteen studies from ten countries did not specific the waterpipe prevalence measure[ 88 , 123 , 129 , 133 – 145 ], the details of which are presented in Table H in S1 File .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, consistent evidence has linked water pipe use to both cigarettes and cannabis use. [17][18][19] A well-established methodology to investigate shared genetic liability between traits is by creating a PRS for one trait, using the estimated effect sizes from a large discovery sample, and then investigate whether this risk score can predict another trait in an independent target sample. 20,21 PRSs represent the genetic load an individual carries regarding a specific trait.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have reported an association between waterpipe use and cigarette smoking [1,13,14]. A few studies have also found that waterpipe use in adolescents is related to other risk behaviours, including use of e-cigarettes [15], snus, alcohol and narcotics [16], as well as gambling [17]. Although waterpipe smoking has been associated with risky health behaviours and can also lead to nicotine dependence [18,19], no prior studies have determined whether such behaviour is also associated with adolescents’ mental well-being.…”
Section: Introductionmentioning
confidence: 99%